2016
DOI: 10.1111/imm.12589
|View full text |Cite
|
Sign up to set email alerts
|

Nasal administration of interleukin‐33 induces airways angiogenesis and expression of multiple angiogenic factors in a murine asthma surrogate

Abstract: SummaryThe T-helper cell type 2-promoting cytokine interleukin-33 (IL-33) has been implicated in asthma pathogenesis. Angiogenesis is a feature of airways remodelling in asthma. We hypothesized that IL-33 induces airways angiogenesis and expression of angiogenic factors in an established murine surrogate of asthma. In the present study, BALB/c mice were subjected to serial intranasal challenge with IL-33 alone for up to 70 days. In parallel, ovalbumin (OVA) -sensitized mice were subjected to serial intranasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 38 publications
6
33
0
Order By: Relevance
“…Previous studies have strongly implicated IL‐33 in playing a key role in the pathogenesis of the airways mucosal inflammation that typically accompanies human asthma . In our own previous studies we showed that direct, per‐nasal application of IL‐33 alone to the murine airway is sufficient to cause asthma‐like inflammation, including subepithelial deposition of collagens .…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Previous studies have strongly implicated IL‐33 in playing a key role in the pathogenesis of the airways mucosal inflammation that typically accompanies human asthma . In our own previous studies we showed that direct, per‐nasal application of IL‐33 alone to the murine airway is sufficient to cause asthma‐like inflammation, including subepithelial deposition of collagens .…”
Section: Discussionmentioning
confidence: 67%
“…Murine surrogates of asthma induced by IL‐33 or OVA challenge were prepared and studied as previously described . Briefly, recombinant murine IL‐33 (rmIL‐33, 100 ng in 50 μl saline; R&D Systems, Minneapolis, MN) or saline control was administered per‐nasally directly to the airways of two groups of mice daily from days 18–23 from the commencement of the experiment, then every 2 days until day 53.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition there is evidence, at least from animal surrogates, that these cytokines can effect many of the aspects of airways remodelling deemed characteristic of asthma, such as neoangiogenesis (5). A range of both endogenous, local stimuli as well as external, environmental stimuli can elicit epithelial release of these cytokines -one such category of stimuli is endogenous and environmental proteases.…”
Section: Editorial For: "Endogenous Protease Inhibitor In Airway Epitmentioning
confidence: 99%